Implementasi Pembelajaran Tatap Muka Terbatas Pada Mata Pelajaran Fikih - Untung Khoiruddin (Universitas Islam Tribakti Lirboyo Kediri, 2023)
This study aims to determine the implementation and impacts of limited face-to-face learning on Fiqh subjects at MAN 3 Nganjuk. This research uses qualitative approach with the case study as its type of research. This research took place at MAN 3 Nganjuk. Data collection were carried out through observation, interviews, and documentation techniques. Data analysis used the Miles Huberman model which includes data reduction, data presentation, and drawing conclusions. In order to check the validity of the data, it was done through extended observation, increased persistence, and triangulation. The results showed that: (1) The limited face-to-face learning process on Fiqh subjects at MAN 3 Nganjuk was carried out through rotation system while still applying the health protocol. (2) The positive impacts of limited face-toface learning including making it easier for both teachers and students to carry out learning, increasing students’ abilities and learning outcomes, and increasing students’ enthusiasm and motivation in learning. While the negative impacts include the lack of maximum learning activities due to limited learning duration, limited activities of students in learning, and the emergence of concerns about the spread of Covid-19 in the school environment.